Coexisting Frailty With Heart Failure - Uchmanowicz, Izabella; Nessler, Jadwiga; Gobbens, Robbert; Gackowski, Andrzej; Kurpas, Donata; Straburzynska-Migaj, Ewa; Kałuzna-Oleksy, Marta; Jankowska, Ewa A. (Frontiers in Physiology, 2019)
People over 65 years of age constitute over 80% of patients with heart failure (HF) and the incidence of HF is 10 per 1000 in people aged above 65 years of age. Approximately 25% of older patients with HF exhibit evidence of frailty. Frail patients with cardiovascular disease (CVD) have a worse prognosis than non-frail patients and frailty is an independent risk factor for incident HF among older people. Planning the treatment of individuals with HF and concomitant frailty, one should consider not only the limitations imposed by frailty syndrome (FS) but also those associated with the underlying heart disease. It needs to be emphasized that all patients with HF and concomitant FS require individualized treatment.